2018
DOI: 10.3389/fvets.2018.00228
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Fate of Cattle Herds With Inconclusive Reactors to the Tuberculin Skin Test

Abstract: Bovine tuberculosis (TB) is an important animal health issue in many parts of the world. In England and Wales, the primary test to detect infected animals is the single intradermal comparative cervical tuberculin test, which compares immunological responses to bovine and avian tuberculins. Inconclusive test reactors (IRs) are animals that demonstrate a positive reaction to the bovine tuberculin only marginally greater than the avian reaction, so are not classified as reactors and immediately removed. In the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
(26 reference statements)
1
10
0
Order By: Relevance
“…TB history (an increasing number of incidents in the herd over the previous 10 years) was significantly associated with the odds of becoming a reactor in the England, HRA, and Wales models, and this correlates with the findings from herd-level studies and the positive association between the positive predictive value of tests with background prevalence of infection [15,28,29]. No association between TB history and the odds of becoming a reactor was observed in the edge area or LRA.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…TB history (an increasing number of incidents in the herd over the previous 10 years) was significantly associated with the odds of becoming a reactor in the England, HRA, and Wales models, and this correlates with the findings from herd-level studies and the positive association between the positive predictive value of tests with background prevalence of infection [15,28,29]. No association between TB history and the odds of becoming a reactor was observed in the edge area or LRA.…”
Section: Discussionsupporting
confidence: 56%
“…Epidemiological analysis showed dairy herds are 9% more likely to have a TB incident than beef herds in England after adjustment for location and herd size [5]. Another study examining risk factors associated with the hazard of a TB incident found no association for herd type, although there was evidence that the hazard of a TB incident among dairy herds increases over time [15]. On an individual animal level, the evidence is limited and variable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Statistical modeling studies are important to elucidate the transmission dynamics of BTB within and between herds (26)(27)(28)(29). Additionally, mathematical modeling studies have been carried out to analyze disease transmission and provide insight into useful control measures (30)(31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%